Exploring education-induced bargaining power of women on household welfare in Sub-Saharan Africa - Raymond Boadi Frempong; David Stadelmann (Economies, 2024)
Women's education and empowerment have engaged the interest of policymakers and academics for many years. We employ individual-level data from Ghana and Uganda in this paper to offer a comparative analysis of the impact of women's education and empowerment on six household welfare indicators: child labor, child school enrollment, female labor force participation, fertility rate, household food expenditure, and nutrition intake. Comparing the two countries is insightful due to their distinct socio-economic structures and cultural contexts, which might influence the dynamics of women's empowerment differently. The study utilizes the Ordinary Least Squares (OLS) and Instrumental Variables (IV) regressions and provides a battery of robustness tests. The empirical results show that in a household, the woman's and man's education levels are significant determinants of household welfare. However, contrary to common assumptions, the woman's education does not have a stronger effect than the man's, and her relative bargaining position has negligible effects on the welfare indicators studied, at least for the cases of Ghana and Uganda. Further sensitivity checks support these findings, suggesting that female education can improve household welfare, but its impact may not necessarily operate through enhanced bargaining power within the household.
Keywords: I02; J13; J16; 330; women empowerment; intra-household bargaining; household welfare; Ghana; Uganda